Dampak Penerapan Standar Akuntansi Pemerintah, Kualitas Laporan Keuangan Dan Sistem Pengendalian Internal Terhadap Akuntabiltas Kinerja Instansi Pemerintah Daerah - Gerry Hamdani Putra; Muhammad Rivandi; Dewi Zulvia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to provide empirical evidence regarding the impact of implementing government accounting standards and internal control systems on the accountability of local government agencies. The population in this study was taken from the Regional Civil Service Agency (BKD) of Padang. The sampling technique that researchers used was Porposive Sampling with a sample size of 40 respondents and the testing tool used was multiple linear regression analysis. The results of this research prove that there is an impact of implementing government accounting standards, the quality of financial reports and internal control systems on the accountability of the performance of local government agencies Keyword: implementing government accounting standards, quality of financial reports, internal control systems, accountability of local government agencies